Designing a Contextual Numeracy Assessment for Adult Learners: Evidence from Readability Testing Based on the PIAAC Framework - Laela Sagita; Niken Wahyu Utami; Nendra Mursetya Somasih Dwipa; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Ahmad Fauzan (Mathematics Education Journal, 2026)
Adult numeracy plays a crucial role in adults’ ability to engage in everyday problem-solving, work, and lifelong learning. However, Indonesia lacks readily accessible assessment tools for contextual numeracy that conform to international standards and are relevant to adult mathematics education. This study reports on the initial development and qualitative evaluation of a contextual numeracy assessment instrument inspired by the Programme for the International Assessment of Adult Competencies (PIAAC), with a focus on its suitability for adult mathematics education. The instrument was developed through domain mapping and item design aligned with the PIAAC numeracy framework, followed by expert validation via focus group discussions (FGD). This qualitative study developed the instrument through three stages: drafting, cultural contextualization, and scoring rules development. Empirical evidence was obtained through readability involving 10 adult participants and cognitive reviews involving eight reviewers, who served as the primary data source for this study. Participants completed selected numeracy items and engaged in brief cognitive interviews using questionnaires. Qualitative data were analyzed using iterative thematic coding, with coding categories refined through consensus discussions, to identify issues related to understanding instructions, interpreting information, and numerical units, and understanding tables and graphs, as well as sources of confusion arising from contextual or representational features. The findings provide preliminary evidence to support continued refinement and future quantitative validation of contextual numeracy assessments for adult learners. From a mathematics education perspective, this study highlights the importance of readability and cognitive review in developing adult numeracy assessments that accurately capture mathematical literacy in real-life contexts. The refined instrument provides a foundation for future quantitative pilot testing and offers methodological insights for the development of contextual numeracy assessments in adult mathematics education.